Penilaian Jenis Dan Frekuensi Polimorfisme Gen Reseptor Adrenergik Beta-2 (Β2ar) Di Malaysia. - Mohd Nor, Siti Romaino (2009)

(untitled)
Beta-2 adrenergic receptor (β2AR) is encoded by an intronless gene on the long arm (q31-q32) of chromosome 5. The gene contains single nucleotide polymorphisms (SNPs),